2019
DOI: 10.1016/j.eurpsy.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of cariprazine in negative symptoms of schizophrenia: Post hoc analyses of PANSS individual items and PANSS-derived factors

Abstract: Background:Negative symptoms in schizophrenia are heterogeneous and multidimensional; effective treatments are lacking. Cariprazine, a dopamine D3-preferring D3/D2 receptor partial agonist and serotonin 5-HT1A receptor partial agonist, was significantly more effective than risperidone in treating negative symptoms in a prospectively designed trial in patients with schizophrenia and persistent, predominant negative symptoms.Methods:Using post hoc analyses, we evaluated change from baseline at week 26 in individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 52 publications
3
91
0
4
Order By: Relevance
“…The overall severity of schizophrenia was assessed using the Positive and Negative Symptoms Scale (PANSS) [19,20]. The scale for the Assessment of Positive Symptoms (SAPS) was used to measure the severity of AHs and VHs.…”
Section: Assessment Of the Severity Of Psychotic Auditory And Visuamentioning
confidence: 99%
“…The overall severity of schizophrenia was assessed using the Positive and Negative Symptoms Scale (PANSS) [19,20]. The scale for the Assessment of Positive Symptoms (SAPS) was used to measure the severity of AHs and VHs.…”
Section: Assessment Of the Severity Of Psychotic Auditory And Visuamentioning
confidence: 99%
“…Total severity of schizophrenia was assessed by the Positive and Negative Symptoms Scale (PANSS) (Fleischhacker et al 2019). The scale for the Assessment of Positive Symptoms (SAPS) (Kumari et al 2017) was used to measure the severity of AHs and VHs.…”
Section: Psychotic Auditory and Visual Hallucination Symptoms Severimentioning
confidence: 99%
“…Data from these 97 patients were used for analysis. Two independent psychiatrists with no involvement in the current study tested the validity of patient subtype divisions using the Auditory Hallucination Rating Scale (Haddock et al 1999) and the PANSS P3 VHs (Fleischhacker et al 2019) item to distinguish AH and VH severity. The four resulting symptom combination groups and diagnostic assessments of the psychiatrists affirmed our artificial divisions.…”
Section: Demographic and Clinical Characteristics Of Participantsmentioning
confidence: 99%
“…Larger comparative studies with other atypical antipsychotics are missing until now. Based on the findings of previously published studies, an advantage of cariprazine in comparison to other antipsychotics was found, particularly in patients with predominantly "negative symptoms" and prolactin increases or weight gain [7,11]. Akathisia, one of the most common side effects, occasionally led to discontinuation of therapy in some studies [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy and safety of cariprazine in the treatment of schizophrenia were proven in four phase II/III studies [3][4][5][6]. Cariprazine was shown to be more effective in reducing negative symptoms of schizophrenia compared to risperidone [7]. Regarding safety and tolerability the available clinical trials suggest that the most frequently reported adverse events are extrapyramidal symptoms, insomnia, and akathisia [8].…”
Section: Introductionmentioning
confidence: 99%